2007
DOI: 10.1080/00926230601098456
|View full text |Cite
|
Sign up to set email alerts
|

Sex Therapy through the Internet for Men with Sexual Dysfunctions: A Pilot Study

Abstract: Results are described of a pilot study of the efficacy of sex therapy through the Internet for thirty-nine men with erectile dysfunction or rapid ejaculation. Treatment consisted of sex therapy (Masters & Johnson, 1970), had a duration of three months, and was conducted entirely through e-mail. Forty-six percent of the participants dropped out. Fourteen (67%) participants reported an improvement of their sexual functioning. Seven (47%) participants reported the improvement had sustained one month after termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 56 publications
2
19
0
1
Order By: Relevance
“…As well as offering convenience and privacy, online therapies can simultaneously draw together a community of clients while maintaining their anonymity (Jones & McCabe, 2011;Leusink & Aarts, 2006;Tate & Zabinski, 2004). Research into the use of Internet-based interventions for sexual dysfunctions is quite limited, but preliminary evidence from studies investigating online CBT treatments for male sexual dysfunction (MSD) suggest that Internet-based treatment may be a suitable alternative to face-to-face sex therapy (Leusink & Aarts, 2006;McCabe, Price, Piterman, & Lording, 2008;van Diest, van Lankveld, Leusink, Slob, & Gijs, 2007;van Lankveld, Leusink, van Diest, Gijs, & Slob, 2009). Data from the study by Leusink and Aarts (2006) demonstrated that 81% of participants had improved erectile function scores at the completion of therapy.…”
Section: Incorporating Mindfulness and Chat Groups Into An Online Cogmentioning
confidence: 99%
“…As well as offering convenience and privacy, online therapies can simultaneously draw together a community of clients while maintaining their anonymity (Jones & McCabe, 2011;Leusink & Aarts, 2006;Tate & Zabinski, 2004). Research into the use of Internet-based interventions for sexual dysfunctions is quite limited, but preliminary evidence from studies investigating online CBT treatments for male sexual dysfunction (MSD) suggest that Internet-based treatment may be a suitable alternative to face-to-face sex therapy (Leusink & Aarts, 2006;McCabe, Price, Piterman, & Lording, 2008;van Diest, van Lankveld, Leusink, Slob, & Gijs, 2007;van Lankveld, Leusink, van Diest, Gijs, & Slob, 2009). Data from the study by Leusink and Aarts (2006) demonstrated that 81% of participants had improved erectile function scores at the completion of therapy.…”
Section: Incorporating Mindfulness and Chat Groups Into An Online Cogmentioning
confidence: 99%
“…Van Diest, van Lankveld, Leusink, Slob, and Gijs (2007) recently conducted a pilot study to gauge the possible efficacy of sex therapy through the Internet for heterosexual men with erectile dysfunction or premature ejaculation. A relatively homogeneous sample was investigated from which men with hypersexuality, and problems with gender identity or sexual orientation were excluded, as were men with depressive symptoms, psychotic comorbidity, substance abuse disorder, and major marital problems.…”
Section: Types Of Self-help For Sexual Dysfunctionsmentioning
confidence: 99%
“…Van Diest et al. [23] reported the results of a pilot study of an Internet‐based sex therapy with 39 men experiencing ED. The treatment consisted of a sex therapy based on the Masters and Johnson [1] approach and which lasted for 3 months and was conducted entirely through e‐mail.…”
Section: Introductionmentioning
confidence: 99%